Pemasaran Jasa Pendidikan di MTs Al-Ikhlas Keban II-Musi Banyuasin - Ibrahim, Ibrahim; Salpiana, Ika; Niswah, Choirun; Febriyanti, Febriyanti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study discusses the process of marketing educational services at MTs Al-Ikhlas Keban II-Musi Banyuasin. The research is qualitative in nature, employing a descriptive approach. Data collection methods include observation, interviews, and documentation. The data analysis techniques involve data collection, data presentation, verification, and drawing conclusions. To ensure the validity of the data, the researcher used triangulation, which consists of time triangulation, method triangulation, and source triangulation. The findings of this research indicate that the marketing of educational services at MTs Al-Ikhlas Keban II has been implemented effectively. The products offered by the madrasah meet the needs and expectations of the users. The marketing of educational services is conducted through a well-organized process and effective educational customer strategies, spreading information about quality and products via social media platforms such as Facebook and Instagram, as well as using banners. This process is also supported by skilled human resources in their respective fields. The marketing costs are covered by the madrasah budget and do not hinder the process. Prospective students are not charged any registration fees. The madrasah is strategically located, surrounded by many residents and several elementary schools/madrasah ibtidaiyah